1978
DOI: 10.1148/126.3.677
|View full text |Cite
|
Sign up to set email alerts
|

Army Technologists: 29-Year Follow Up for Cause of Death

Abstract: A previous 18-year follow-up study revealed no significant excess of cancer among men who served in the Army during World War II as radiological technologists (n = 6,560) as compared with men who served as medical, laboratory, or pharmacy technologists (n = 6,826). Extension of the follow up by 11 years (1946-1974) revealed that 145 former radiological technologists had died of cancer, as compared with 158 controls. No statistically significant differences were found between these groups for individual sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 5 publications
3
13
1
Order By: Relevance
“…Our results are consistent with Wndings from cohort mortality studies conducted in US, Canadian and UK atomic energy workers (Cardis et al 1995;Gilbert et al 1989Gilbert et al , 1993Lui et al 1992;Wiggs et al 1991;Darby et al 1993;Kendall et al 1992) and studies of Xray workers in China (Wang et al 1990) and the US military (Jablon and Miller 1978) in not showing an increase in risk of NHL with increasing exposure to ionizing radiation. Our results are also similar to those from a population-based case control study in the US where exposure was assessed by way of a job-exposure matrix (JEM) speciWcally-designed to assess ionizing radiation (Eheman et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with Wndings from cohort mortality studies conducted in US, Canadian and UK atomic energy workers (Cardis et al 1995;Gilbert et al 1989Gilbert et al , 1993Lui et al 1992;Wiggs et al 1991;Darby et al 1993;Kendall et al 1992) and studies of Xray workers in China (Wang et al 1990) and the US military (Jablon and Miller 1978) in not showing an increase in risk of NHL with increasing exposure to ionizing radiation. Our results are also similar to those from a population-based case control study in the US where exposure was assessed by way of a job-exposure matrix (JEM) speciWcally-designed to assess ionizing radiation (Eheman et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In our analysis, occupational radiation exposure was not related to an increased risk of NHL. Our ®ndings are consistent with ®ndings from cohort mortality studies conducted in U.S., Canadian, and U.K. nuclear workers [Cardis et al, 1995;Gilbert et al, 1989Gilbert et al, , 1993Lui 1992;Wiggs et al, 1991;Darby et al, 1993;Kendal et al, 1992], and studies of x-ray technicians in China [Wang et al, 1990] and in the U.S. military [Jablon and Miller, 1978].…”
Section: Discussionsupporting
confidence: 90%
“…U.S. and other radiologists first employed prior to 1940 [2][3][4][5][6][7] experienced elevated risks of leukemia, skin cancer and other malignancies, but cancer risks were not generally increased among radiologists first employed after 1940 (with the possible exception of multiple myeloma among U.S. radiologists). 4,5 Some, 7,8 but not all, 9,10 cohorts of radiologic technologists experienced an elevated leukemia risk. None of the earlier studies reported risks in relation to individual lifetime work histories, and only a few 7,10 included female technologists.…”
mentioning
confidence: 99%